Evaluation of cardiopulmonary exercise testing, heart function, and quality of life in children after allogenic hematopoietic stem cell transplantation. Issue 1 (14th October 2018) - Vandekerckhove, Kristof; De Waele, Kathleen; Minne, Aurelie; Coomans, Ilse; De Groote, Katya; Panzer, Joseph; Dhooge, Catherine; Bordon, Victoria; De Wolf, Daniel; Boone, Jan
Abstract: Background: Physical fitness is an important determinant of quality of life (QOL) after hematopoietic stem cell transplantation. Cardiac function can influence exercise performance. The aim of this study was to assess these factors and their interrelationship. Procedure: Children underwent cardiopulmonary exercise testing (CPET) at least 1 year after hematopoietic stem cell transplantation (HSCT) and were compared with healthy controls. Systolic and diastolic heart function and left ventricle (LV) wall dimensions were measured. Health‐related QOL (HR‐QOL) was evaluated using PedsQL questionnaires. Results: Forty‐three patients performed CPET (26 boys, 13.6 ± 3.4 years, weight 45.5 ± 13.3 kg, length 152.9 ± 17.5 cm, body surface area 1.35 ± 0.28). HSCT patients had lower maximal oxygen consumption (VO2peak/kg, 34.7 ± 8.4 vs 46.3 ± 7.1 mL/kg/min, P < 0.001), shorter exercise duration (9.1 ± 2.5 vs 12.9 ± 2.6 min, P < 0.001), and lower maximal load (%Ppeak 70.8 ± 19.7 vs 102.4% ± 15.9%, P < 0.001). Echocardiography demonstrated decreased interventricular septal wall thickness (interventricular septum in diastole [IVSd] Z ‐value −0.64 ± 0.69, P < 0.001), and more systolic (11% of patients) and diastolic dysfunction (high E / E ' Z ‐value 1.06 ± 1.13, P < 0.001). LV dilatation correlates with VO2max/kg ( r = −0.364, P = 0.017). HR‐QOL showed lower overall and emotional functioning scores (respectively, P = 0.016 and P = 0.001). Patients after anthracycline therapy have the lowest maximal exercise performance, but have no difference in QOL. Diminished exercise performance is not encountered as a QOL limitation. Total body irradiation influences the domain of psychosocial functioning. Conclusions: LV (systolic and diastolic) and right ventricle dysfunctions justify the need for thorough cardiac follow‐up in children after HSCT. Lower physical fitness levels and lower HR‐QOL emphasize the importance of CPET and fitness programs.